Biotechnological production of galactooligosaccharides (GOS) using porungo cheese whey - BOLOGNESI,Lais Saldanha (2022)
Abstract The bioconversion of porungo cheese whey into galactooligosaccharides (GOS) was investigated using immobilized β-galactosidase in batch system. Two enzymatic immobilization strategies were tested for optima pH and temperature and the best immobilization strategy was used to evaluate the GOS production in two steps. First, different lactose sources (substrates) were tested, and subsequently, different concentrations of porungo cheese whey (200 g L-1 and 400 g L-1) and temperatures (37 °C to 46 °C) were evaluated. Immobilization of β-galactosidase increased the range of operational pH (7.0-7.5) when immobilized in calcium-alginate support. However, the pH range decreased when the immobilization was conducted using calcium-Concanavalin A support. Batch reactions using the calcium-alginate immobilized biocatalyst produced the highest yields of GOS (63.2%) from porungo cheese whey, compared to the control substrate of lactose solution at concentration of 50 g L-1 (41.1%). The temperature of 46 °C and 400 g L-1 of substrate shown the better condition to GOS production, with lactose conversion of 61.4%. These results suggest the possible use of porungo cheese whey as substrate in the biotechnological production of GOS.